Short-Term Physical Inactivity Induces Endothelial Dysfunction - Bowden Davies, Kelly A.; Norman, Juliette A.; Thompson, Andrew; Mitchell, Katie L.; Harrold, Joanne A.; Halford, Jason C. G.; Wilding, John P. H.; Kemp, Graham J.; Cuthbertson, Daniel J.; Sprung, Victoria S. (Frontiers in Physiology, 2021)
Objective This study examined the effects of a short-term reduction in physical activity, and subsequent resumption, on metabolic profiles, body composition and cardiovascular (endothelial) function. Design Twenty-eight habitually active (≥10,000 steps/day) participants (18 female, 10 male; age 32 ± 11 years; BMI 24.3 ± 2.5 kg/m2) were assessed at baseline, following 14 days of step-reduction and 14 days after resuming habitual activity. Methods Physical activity was monitored throughout (SenseWear Armband). Endothelial function (flow mediated dilation; FMD), cardiorespiratory fitness (V.⁢O2 peak) and body composition including liver fat (dual-energy x-ray absorptiometry and magnetic resonance spectroscopy) were determined at each assessment. Statistical analysis was performed using one-way within subject’s ANOVA; data presented as mean (95% CI). Results Participants decreased their step count from baseline by 10,111 steps/day (8949, 11,274; P < 0.001), increasing sedentary time by 103 min/day (29, 177; P < 0.001). Following 14 days of step-reduction, endothelial function was reduced by a 1.8% (0.4, 3.3; P = 0.01) decrease in FMD. Following resumption of habitual activity, FMD increased by 1.4%, comparable to the baseline level 0.4% (–1.8, 2.6; P = 1.00). Total body fat, waist circumference, liver fat, whole body insulin sensitivity and cardiorespiratory fitness were all adversely affected by 14 days step-reduction (P < 0.05) but returned to baseline levels following resumption of activity. Conclusion This data shows for the first time that whilst a decline in endothelial function is observed following short-term physical inactivity, this is reversed on resumption of habitual activity. The findings highlight the need for public health interventions that focus on minimizing time spent in sedentary behavior.